Detection of telomerase in hepatocellular carcinomas using a PCR ELISA assay: comparison with hTR expression. Issue 10 (1st October 1999) - Ferlicot, S; Paradis, V; Dargère, D; Monges, G; Bedossa, P
Abstract : BACKGROUND: While telomerase is undetectable in most normal somatic tissues, telomerase activation has been detected in many immortal cell lines and various cancers. AIM: To investigate telomerase expression in hepatocellular carcinoma, and to assess the expression of the RNA component of telomerase, hTR. METHODS: 39 hepatocellular carcinomas were studied using a telomerase polymerase chain reaction (PCR) enzyme linked immunosorbent assay, which does not require radioactive PCR amplification and yields a semiquantitative measurement. Expression of hTR was also assessed by a non-radioactive in situ hybridisation procedure. The correlations between these two markers and the clinicopathological data were analysed. RESULTS: Telomerase activity was detected in 23 of 39 hepatocellular carcinoma specimens (59%). Comparison of hepatocellular carcinoma with and without telomerase expression, or with high and low telomerase (10 cases v 13 cases), showed no differences in the principal clinicopathological data. Although median survival was lower in the group with detectable telomerase activity than in that with undetectable activity (510 v 720 days) the difference was not significant (log-rank test, p = 0.08). hTR expression was detected in 11 of 14 cases of hepatocellular carcinoma tested (78%) and in four of 12 samples of adjacent non-cancerous tissue (33%). Five tumours and four non-cancerous tissues were positive for hTR, whereas no telomerase activity was detected in these. CONCLUSIONS: The presence of telomerase activity in hepatocellular carcinomas is confirmed. No correlation was observed between clinicopathological data and telomerase expression in hepatocellular carcinoma, but survival seemed better in the absence of telomerase expression. hTR seems to be more widely expressed than telomerase.